National Health Interview Survey, 1994: Family Resources Income and Assets Supplement ([Verlag nicht ermittelbar], 1999)
The purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. This supplement contains edited and imputed data for the Income and Assets portion (Part D) of the 1994 NHIS Family Resources questionnaire. Other components of the Family Resources questionnaire cover Access to Care (Part A), Health Care Coverage (Part B), and Private Plan and Coverage Detail (Part C). The Income and Assets supplement contains variables from the NHIS core Person File (see NATIONAL HEALTH INTERVIEW SURVEY, 1994 [ICPSR 2533]), including sex, age, race, marital status, veteran status, education, income, industry and occupation codes, and limits on activity. Other items focus on employment, income from employment and businesses, other income sources including retirement and Social Security, and asset holdings such as cars, houses, businesses, and investment properties. Additional information on the receipt of income from public programs like Aid to Families with Dependent Children (AFDC), Supplemental Security Income (SSI), and food stamps is also included.